Influence of Fixed and Removable Appliances on the Periodontal Health of Orthodontic Patients - Yen, En-Tse (Archive of Orofacial Data Science, 2025)
AIM: To explore the differences in the impact of fixed appliances and clear aligners on periodontal disease, specifically examining the plaque index (PI), bleeding on probing (BOP), and probing depth (PD). METHODS: A search for relevant literature published in English over the past decade was conducted on PubMed, along with a manual search from December 2023 to January 2024, yielding 10,890 hits. After reviewing titles and abstracts, and applying publication year filters, 1,096 papers were selected for full-text analysis. Following exclusions of duplicates and irrelevant studies, 21 publications were identified for systematic evaluation. RESULTS: The studies indicated that fixed appliances generally resulted in higher PD, PI, and BOP values compared to removable appliances. Furthermore, fixed appliances were associated with poorer periodontal outcomes than control groups without orthodontic treatment, and significant worsening of periodontal parameters was noted in patients using fixed appliances. CONCLUSION: This systematic review suggests that fixed orthodontic appliances may have a greater negative impact on periodontal health than removable appliances. Although differences in PD, PI, and BOP were statistically significant, their clinical relevance may be limited.